Pengaruh Putaran Spindle Dan Bahan Spesimen Terhadap Gaya Potong Pada Proses Pemesinan Turning - Sucipto, Hadi; Nasution, Arya Rudi; Umurani, Khairul; Siregar, Ahmad Marabdi (Fakultas Teknik UMSU, 2022)
The turning Machining Process is one of the most commonly used machining processes in the industrial world, both in large-scale industries and small industries (home industries). The turning machining process is a process of changing the shape of the material by removing some of the material in the form of swells. During the machining process, there is an interaction between the tool and the workpiece specimen being cut which results in a change in the cutting force. The value of the cutting force is important information in research, this study aims to see the cutting force during the turning machining process using 2 different types. The research data collection method uses sensor tools, there are three sensors, namely the load cell sensor for cutting force, the photoelectric counter module for rotation (rpm), and the thermocouple for feeding temperature. The research variable used is the rotational speed of rpm starting from 90, 110, 150, and 190 rpm, the depth of cut is 0.3 mm. The cutting force generated on the DCGT insert chisel is 5.94N at 90 rpm, 4.13N at 110 rpm, 2.38N at 150 rpm, and at 190 rpm the DCGT chisel gets a force of 2.03N. Furthermore, the cutting force that occurs on the DCMT insert chisel is 2.94N at 90 rpm, 2.67N at 110 rpm, 2.61N at 150 rpm, and at 190 rpm the DCMT insert chisel gets a force of 2.51N. It can be concluded that the decrease in cutting force is influenced by the amount of rpm used, and the magnitude of the cutting force is due to vibrations that occur in the specimen caused by low rpm.